Antioxidant and Anti-Inflammatory Effects in RAW264.7 Macrophages of Malvidin, a Major Red Wine Polyphenol - Bognar, Eszter (Public Library of Science, 2013)
BACKGROUND: Red wine polyphenols can prevent cardiovascular and inflammatory diseases. Resveratrol, the most extensively studied constituent, is unlikely to solely account for these beneficial effects because of its rather low abundance and bioavailability. Malvidin is far the most abundant polyphenol in red wine; however, very limited data are available about its effect on inflammatory processes and kinase signaling pathways. METHODS & FINDINGS: The present study was carried out by using RAW 264.7 macrophages stimulated by bacterial lipopolysaccharide in the presence and absence of malvidin. From the cells, activation of nuclear factor-kappaB, mitogen-activated protein kinase, protein kinase B/Akt and poly ADP-ribose polymerase, reactive oxygen species production, mitogen-activated protein kinase phosphatase-1 expression and mitochondrial depolarization were determined. We found that malvidin attenuated lipopolysaccharide-induced nuclear factor-kappaB, poly ADP-ribose polymerase and mitogen-activated protein kinase activation, reactive oxygen species production and mitochondrial depolarization, while upregulated the compensatory processes; mitogen-activated protein kinase phosphatase-1 expression and Akt activation. CONCLUSIONS: These effects of malvidin may explain the previous findings and at least partially account for the positive effects of moderate red wine consumption on inflammation-mediated chronic maladies such as obesity, diabetes, hypertension and cardiovascular disease.